Parasitoid searching behavior driven by volatiles induced on transgenic maize by bt-resistantand susceptible Spodoptera frugiperda - Ribas, Natália de Souza (2022)
The development and use of toxins from Bacillus thuringiensis (Bt) to control the main lepidopteran maize pests` populations has been used since 1996. This technology positively impacts agricultural production, causing a reduction in the use of pesticides, minimal effect on non- target organisms, and reduced environmental impact. However, this large-scale cultivation is configured in an environment with a high-pressure selection for resistance. Therefore, there are already many documented cases of resistance in the field, resulting in pest control failures for many Bt toxins. Nevertheless, when there is a cost associated with resistance, individuals with resistance alleles could perform less in the absence of Bt toxin than the Bt-susceptible. This may help slow down the spread of resistance alleles because it can favor susceptible individuals instead the resistant ones. A diversity of fitness costs has been associated with developing and reproducing of resistance in lepidopteran insects. Those are costs affecting the individual directly. However, an related indirect cost, such as being more vulnerable to the attack of natural enemies, has received less attention. It is known that plants under attack with eggs oviposited or larvae feeding can use indirect defenses to attract natural enemies. Moreover, Bt and isogenic plants can emit different amounts of volatiles. Therefore, this study aimed to verify possible indirect costs related to changes in the amount of volatiles emitted by Bt and non-Bt maize plants when oviposited and fed by Spodoptera frugiperda and how this affects the eggs parasitoid Trichogramma pretiosum. For the egg deposition, our results demonstrated that T. pretiosum females preferred volatiles emitted by isogenic maize varieties with eggs of either susceptible or resistant S. frugiperda rather than the odors from control plants without eggs. The females did not discriminate between control and plants with S. frugiperda eggs on the Bt maize varieties. This pattern could be due to the induction of green leaf volatiles ((E)-2-hexenal and (Z)-3-hexenal) observed in the isogenic plants but not in the Bt varieties. For larvae feeding, our results demonstrated that T. pretiosum females preferred volatiles emitted by isogenic maize plants treated with the oral secretion of Bt-susceptible insects to resistant populations induced plants. On the other hand, in Bt plants, they preferred plants treated with regurgitant from resistant populations than Bt-susceptible regurgitant. These results agree with the plants' total volatile; the T. pretiosum chose the plants that emitted the highest amounts of volatiles. Thus, these results may help optimize the biological control with T. pretiosum in maize fields with Bt and isogenic refuge areas to control S. frugiperda by promoting the attraction of T. pretiosum wasps. Therefore, our study unravels the effects of an ecological disadvantage for the resistant insects in the Bt field, which could help delay the evolution of the resistance. Keywords: Tritrophic interaction. Fall armyworm. Induced defense. Maize. Bt. Volatiles